PENGARUH STRUKTUR KEPEMILIKAN PEMERINTAH, DOMESTIK, ASING, MODEL BANK DAN KONSENTRASI KEPEMILIKAN PADA KINERJA KEUANGAN PERBANKAN - Dianitasari, Nadya; Hersugondo, Hersugondo (Diponegoro Journal of Management, 2020)
This study aims to analyze the effect of banks model, the different types of ownership, and ownership concentration on bank financial performance. State ownership, domestic ownership and foreign ownersip were used as the ownership indicators and Net Interest Margin (NIM) ratio were used as the proxied of financial performance. The Population that was used in this research consisted of all conventional and islamic commercial banks which is listed in Directory of Indonesian Banking 2018 and published the financial statements during 2014-2019. After passed the purposive sampling method there were 94 banks obtained as samples. The data analysis technique used is descriptive statistic, classical assumption testÂ  and panel regression test with random effect model. The result of this research showed that banks model and state ownership have positively significant impact on NIM and foreign ownership has negatively significant impact while domestic ownership and ownership concentration have insignificantly impact on bank financial performance.Â